2019
DOI: 10.20945/2359-3997000000177
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association between vitamin D levels and polycystic ovary syndrome (PCOS) phenotypes?

Abstract: Objective: The aim of this study was to assess the serum vitamin D level in a retrospective study in women with polycystic ovary syndrome (PCOS), according to the different phenotypes of the disease. Subjects and methods: In this retrospective study, the records of 351 infertile women who were diagnosed with PCOS were examined, and 200 of them were enrolled in the study randomly in 4 PCOS phenotypes. Fifty normal ovulatory women with the history of male factor were selected as the control group. Parameters, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
3
16
0
1
Order By: Relevance
“…Our results point out the role of vitamin D in the pathogenesis of PCOS.Vitamin D by itself can be a cause of PCOS. Evidences verify that vitamin D plays an essential role in reproductive activities and that the reproductive system, including ovaries, the endometrium, and the placenta, has receptors forvitamin D. Also, it has been found that calcium dysregulation, a condition related to vitamin D deficiency, is responsible for the increase in the follicular arrest and results in menstrual and fertility disorders in women with PCOS [22].ThePCOS group in our study had a significantly lower vitamin D concentration than the control group. Only 6.89% of PCOS patients and 10.34% of controls in our study had HTN (Table 1) and they lied in the vitamin D deficient category only (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results point out the role of vitamin D in the pathogenesis of PCOS.Vitamin D by itself can be a cause of PCOS. Evidences verify that vitamin D plays an essential role in reproductive activities and that the reproductive system, including ovaries, the endometrium, and the placenta, has receptors forvitamin D. Also, it has been found that calcium dysregulation, a condition related to vitamin D deficiency, is responsible for the increase in the follicular arrest and results in menstrual and fertility disorders in women with PCOS [22].ThePCOS group in our study had a significantly lower vitamin D concentration than the control group. Only 6.89% of PCOS patients and 10.34% of controls in our study had HTN (Table 1) and they lied in the vitamin D deficient category only (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, there is no agreement on the differences in serum vitamin D levels among women having and not having PCOS. Many studies reported that vitamin D of patients with PCOS wasinversely correlated with metabolic disturbances [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Increased risk of PCOS or its associated endocrine/metabolic disturbances were linked with polymorphism of vitamin D receptor gene, which presents the effect of vitaminD in PCOS pathogenesis [12,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…This was in agreement with Eftekhar et al study. 9 They showed that AMH was significantly higher in PCO patients. Also, Bhide et al showed that women with PCO morphology had significantly higher AMH levels than women in the control group.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, Eftekhar et al study showed that a lower serum VD level in the PCOS patients than in control patients (p<0.001). 9 This may be contributed to ethnic group or geographical factors or different lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Проводились исследования и по оценке уровня витамина D в сыворотке крови у пациенток с СПКЯ в зависимости от фенотипа заболевания, однако достоверных различий в уровне витамина D при различных фенотипах СПКЯ не обнаружено [42].…”
Section: лечениеunclassified